Propriedades eletrônicas, estruturais e constantes elásticas do ZnO Structural, electronic properties and elastic constants of ZnO - Naiara Letícia Marana; Julio Ricardo Sambrano; Aguinaldo Robinson de Souza (Química Nova, 2010)
The electronic, structural properties and elastic constants of the wurtzite phase of zinc oxide, ZnO, was investigated using computer simulation at Density Functional Theory level, with B3LYP hybrid functional and Hartree-Fock methodology. The electronic properties as well the band energy was investigated through the analysis of the band structures and density of states (DOS), and the mechanical properties was studied through the calculus of the elastic constants C11, C33, C44, C12 e C13. The results are in good agreement with experimental data found in the literature and in accordance with results obtained by another theoretical methodology.